2014
DOI: 10.1007/s13361-014-0920-1
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Collision Cross-Section Profiling on a Traveling Wave Ion Mobility Mass Spectrometer

Abstract: Ion mobility (IM) is a gas-phase electrophoretic method that separates ions according to charge and ion-neutral collision cross-section (CCS). Herein, we attempt to apply a travelling wave (TW) IM polyalanine calibration method to shotgun proteomics and create a large peptide CCS database. Mass spectrometry methods that utilize IM, such as HDMSE, often use high transmission voltages for sensitive analysis. However, polyalanine calibration has only been demonstrated with low voltage transmission used to prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 53 publications
(68 reference statements)
10
47
0
Order By: Relevance
“…, hydrocarbons and metabolites; 6%) representing the remainder of values. The focus on peptide and protein work can be rationalized as being a result of continued efforts for adapting ion mobility technologies to proteomics workflows, 127129 but also a practical consequence of both the ease of generating large pools of peptides derived from enzymatic digestion 130 and the fact that the structural and charge-state heterogeneity of proteins necessitates the reporting of many CCS values for a single protein. 131134 …”
Section: Composition Of Measurementsmentioning
confidence: 99%
“…, hydrocarbons and metabolites; 6%) representing the remainder of values. The focus on peptide and protein work can be rationalized as being a result of continued efforts for adapting ion mobility technologies to proteomics workflows, 127129 but also a practical consequence of both the ease of generating large pools of peptides derived from enzymatic digestion 130 and the fact that the structural and charge-state heterogeneity of proteins necessitates the reporting of many CCS values for a single protein. 131134 …”
Section: Composition Of Measurementsmentioning
confidence: 99%
“…Like other TWIMS calibration strategies [25,30,33,50,[53][54][55], the procedure used here relies on drift tube reference data Ω ref measured in He. Calibrated TWIMS Ω values therefore represent Beffective^He collision cross sections, although TWIMS uses N 2 as IMS gas [33,60].…”
Section: Twims Calibrationmentioning
confidence: 99%
“…Cone voltages greater than 100 V start to cause calibrant breakdown by CID (Supporting Figure S1) [67], thereby identifying the upper limit of the useful parameter space. The fact that the TWIMS profiles of many calibrant ions depend on the level of collisional activation represents a problem [54,60]. A reliable calibration requires TWIMS and drift tube reference data to be acquired using the same level of activation.…”
Section: Twims Calibration Using Collisionally Heated Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Calibrants were the [M+H] + ions of polyalanine oligomers whose˝values had been previously established by standard DC-drift tube IM-MS experiments [36,37] Several studies have shown that CCSs estimated by the described procedure, i.e. from calibrated T-wave devices, and CCSs measured with drift tube ion mobility instrumentation differ by less than ±3% [33,35,[38][39][40][41]. When this uncertainty is combined with the reproducibility of our drift time measurements (±<1%) and the error reported for the calibrant CCSs (±<1%), the experimental errors for the CCS values reported in this study fall within ±3-4%.…”
Section: Instrument Calibration For the Acquisition Of Collision Crosmentioning
confidence: 99%